2020
DOI: 10.1109/access.2019.2961678
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Project Managers to Implement Industry 4.0-Related Projects

Abstract: The 4 th Industrial Revolution is challenging the ways we are working at all fronts. Its impact is felt in families, organisations and communities. The impact on organisations and particularly working environments is still largely an unknown. Part of the working environment entails the way project teams should be managed. Speed and agility are required to implement the various technologies that form the underlying basis of the 4 th Industrial Revolution. This requires project teams and project managers to adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Digital transformation in the workplace is a phenomenon that causes significant changes in how workers perform tasks, processes, engage in social relationships, and workplace experiences (Meske & Junglas, 2020;Pejic-Bach et al, 2020;Romero-Gázquez & Bueno-Delgado, 2018), and the incorporation of technological applications creates uncertainty owing to the possible replacement of human labor by digital technologies. Therefore, the authors propose that new technologies arising from the Fourth Industrial Revolution should be investigated, analyzed, and adapted by companies' knowledge management to ensure the inclusion of digital jobs (Ana et al, 2019;Marnewick & Marnewick, 2020). This may decrease the resistance to change (Cheng & Hahm, 2019) and prepare companies for a consolidated digital culture (Molino et al, 2020).…”
Section: Hr-digitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital transformation in the workplace is a phenomenon that causes significant changes in how workers perform tasks, processes, engage in social relationships, and workplace experiences (Meske & Junglas, 2020;Pejic-Bach et al, 2020;Romero-Gázquez & Bueno-Delgado, 2018), and the incorporation of technological applications creates uncertainty owing to the possible replacement of human labor by digital technologies. Therefore, the authors propose that new technologies arising from the Fourth Industrial Revolution should be investigated, analyzed, and adapted by companies' knowledge management to ensure the inclusion of digital jobs (Ana et al, 2019;Marnewick & Marnewick, 2020). This may decrease the resistance to change (Cheng & Hahm, 2019) and prepare companies for a consolidated digital culture (Molino et al, 2020).…”
Section: Hr-digitalizationmentioning
confidence: 99%
“…It is necessary to understand the changes related to leadership because traditional leadership is not compatible with interconnected humans and machines (Cortellazzo et al, 2019;Zakaria et al, 2019). Traditional styles are being replaced by ambidextrous leadership, showing flexibility of behavior (Rosing et al, 2011), which creates positive change through transformation (Marnewick & Marnewick, 2020;Sarwono & Bernarto, 2020). For the digital culture to be consolidated by companies, this transformation is a challenge that must be overcome (Zakaria et al, 2019).…”
Section: Hr-strategymentioning
confidence: 99%
“…However, the authors argued whether adopting the Industry 4.0 technologies increase agility in a dynamic way [138,139], or whether adopting the Industry 4.0 technologies presents a change management challenge [140]. Moreover, it is suggested that the change induced by adopting Industry 4.0 technologies is not ordinary but rather a radical change in culture, structure and operations of organizations [139,[141][142][143]. Thus, only organizations which develop a nascent capability of agility will be better off by adopting Industry 4.0 technologies [107,[144][145][146].…”
Section: Aspect Of Agility In Industry 40mentioning
confidence: 99%
“…There is currently a debate on the best ways to manage project teams during the Fourth Industrial Revolution. According to research conducted by Marnewick and Marnewick, the best leadership style for Industry 4.0 projects is defined as servant-leadership, according to which the position of the project manager is not due to his formal power and attributes but skills and knowledge [74], (p. 314). This style is in contradiction with the conditions of management in a traditional organization with a functional structure.…”
Section: Blurring Of the Boundaries Of Operational Managementmentioning
confidence: 99%